PEMBELAJARAN TOLAK PELURU DENGAN PERMAINAN BOLA MERIAM SISWA KELAS V SEKOLA DASAR (Department of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this research is the development seeks to produce a learning model shot put through a cannon ball game for the fifth grade students of elementary schools in penjasorkes learning so as to improve various aspects of learning and improving student ativitas. This study is a research method development. The analysis procedure includes product development product that will be developed, developing initial products, expert validation and revision, testing and revision small group, large group and test the final product. The data was collected using field observations and questionnaires were obtained from expert evaluation and the results of the questionnaires by students. The data analysis technique used is descriptive percentages. From the test results obtained by the expert evaluation data, expert sports physical education and health 94.6% (very good), learning experts I 93.3% (very good), a learning II 96% (very good). Currently student questionnaire data on a small test group obtained the answer by the percentage of 83% with a very good category. And data from the student questionnaire testing large groups obtained the answer by 88.6% percentage of the very good category. Based on the research data, it was concluded that the cannon ball game effectively and in accordance with the characteristics of students that can be used in teaching physical education and sports health.